Unveiling interactions between intervertebral disc morphologies and mechanical behavior through personalized finite element modeling - Muñoz-Moya, Estefano; Rasouligandomani, Morteza; Ruiz Wills, Carlos; Chemorion, Francis Kiptengwer; Piella, Gemma; Noailly, Jérôme (Frontiers in Bioengineering and Biotechnology, 2024)
Intervertebral Disc (IVD) Degeneration (IDD) is a significant health concern, potentially influenced by mechanotransduction. However, the relationship between the IVD phenotypes and mechanical behavior has not been thoroughly explored in local morphologies where IDD originates. This work unveils the interplays among morphological and mechanical features potentially relevant to IDD through Abaqus UMAT simulations. A groundbreaking automated method is introduced to transform a calibrated, structured IVD finite element (FE) model into 169 patient-personalized (PP) models through a mesh morphing process. Our approach accurately replicates the real shapes of the patient's Annulus Fibrosus (AF) and Nucleus Pulposus (NP) while maintaining the same topology for all models. Using segmented magnetic resonance images from the former project